Effect of Geometry on the Dissolution Behaviour of Complex Additively Manufactured Tablets - Seyedebrahim Afkhami; Meisam Abdi; Reza Baserinia (Journal of Manufacturing and Materials Processing)
Additive manufacturing (AM) processes, such as fused deposition modelling (FDM), have emerged as transformative technologies in pharmaceutical manufacturing, enabling the production of drug delivery systems with complex and customised geometries. These advancements provide precise control over drug release profiles and facilitate the development of patient-specific medicines. This study investigates the dissolution behaviour of AM-fabricated tablets made from polyvinyl alcohol (PVA), a hydrophilic and biocompatible polymer widely used in drug delivery systems. The influence of the initial mass, surface area, and surface-area-to-volume ratio (S/V) on dissolution kinetics is evaluated for tablets with intricate geometries. Our findings demonstrate that these parameters, while critical for conventional tablet shapes, are insufficient to fully predict the dissolution behaviour of complex geometries. Furthermore, this study highlights how geometric modifications can enable the administration of the same drug dosage through sustained or immediate release profiles, offering enhanced versatility in drug delivery. By leveraging the geometric design freedom provided by AM technologies, this research underscores the potential for optimising drug delivery systems to improve therapeutic outcomes and patient compliance.